Decolonizing ESG: Magar Rituals ‘Bhume Puja’ and ‘Harelo Parba’ as Indigenous Environmental Frameworks - Rana, Kul Bahadur (Mindscape: A Journal of English & Cultural Studies, 2025)
Indigenous people practise numerous environment friendly practices; however, foreshadowed in recently mainstreamed ESG models. This article explores how indigenous Magar rituals -Bhume Puja (Earth Worship) and Harelo Parba (Festival of Greenery) can be understood as culturally rooted alternatives to dominant Environmental, Social, and Governance (ESG) frameworks. While ESG models are widely promoted as global standards for sustainability, they often reflect technocratic, Western-centric epistemologies that marginalize indigenous knowledge systems. Similarly, grounded in postcolonial and decolonial theories by Spivak, Bhabha, Mignolo, Santos, and Smith, this study critiques the epistemic exclusion inherent in conventional ESG discourses. Following qualitative methods, including ethnographic observations, textual analysis, and a comparative ESG lens, the paper analyses how these Magar rituals embody principles of environmental stewardship (caretaking), social cohesion, and ethical governance. Bhume Puja enacts reciprocal relationships with nature and spiritualized land ethics, while Harelo Parba emphasizes ecological regeneration, intergenerational knowledge transmission, and communal harmony. Both rituals reflect indigenous sustainability logics that challenge extractivist (resource intensive) development and promote cultural resilience. Furthermore, these practices assert Magar identity in the face of ongoing cultural erasure and contribute to epistemic justice by re-centering indigenous worldviews. The study calls for the recognition, respect, and integration of such indigenous frameworks into sustainability discourse, policy, and education as part of a broader effort to decolonize environmental governance and reimagine ESG through pluralist, locally grounded perspectives.